A Review on Recent Progress of Stingless Bee Honey and Its Hydrogel-Based Compound for Wound Care Management - Esa N.E.F.; Ansari M.N.M.; Razak S.I.A.; Ismail N.I.; Jusoh N.; Zawawi N.A.; Jamaludin M.I.; Sagadevan S.; Nayan N.H.M. (MDPI, 2023)
antiinflammatory agent; antioxidant; animal; bee; honey; hydrogel; wound healing; Animals; Anti-Inflammatory Agents; Antioxidants; Bees; Honey; Hydrogels; Wound Healing